KREATIFITAS MEMBACA AL-QUR’AN MELALUI METODE THORIQOTY DI SDI 2 POJOK KOTA KEDIRI - Muhammad Izzul Islami; Marita Lailia Rahman; Anta Gusnanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Reading the Qur’an is an essential basic skill for every Muslim, not only as a form of worship but also as a means of understanding Islamic teachings and developing spiritual character. This study examines the application of the Thoriqoty method in enhancing Qur’an reading creativity among students at SDI 2 Pojok, Kediri. The Thoriqoty method offers a varied and flexible approach, combining drills, demonstrations, immediate feedback, and progress monitoring to foster students’ reading skills, religious attitudes, discipline, and self-confidence. A descriptive-analytical qualitative approach was employed through a case study, with data collected from interviews, observations, and documentation involving teachers, students, and parents. The results indicate that this method is effective in improving Qur’an reading skills and establishing students’ spiritual foundations; however, it still faces challenges such as varying learning motivation, limited independent practice, restricted individual attention from teachers, and suboptimal facilities. This study emphasizes the importance of strengthening teachers’ pedagogical competence, enhancing students’ internal motivation, and providing adequate learning resources so that the Thoriqoty method can cultivate a generation of young people who are proficient in reading the Qur’an and well-developed in both character and spirituality.